Analysis of children’s deaths epidemic in Talara during the 1997-1998 El Niño Phenomenon: ¿are we prepared to face another one? - Del Águila, Aníbal (2007)
World climate changes due to global warming causes increasing concern because of its impact on health and particularly its influence on the so called emerging infections. A poorly understood aspect of emerging infections is changes in virulence and clinical manifestations of known pathogens. The Talara province epidemic with a great number of children deaths during the 1997-1998 El Niño phenomenon was produced by an unusual clinical disease with quick progression and high mortality. The clinical symptoms sequence, physical examination and laboratory data showed a viral infection pattern. The clinical neurological symptoms was due to encephalitis, and cerebral edema was the cause of death of these children. Many known viruses were probably responsible like arboviruses, influenza viruses, parainfluenza, adenoviruses, echoviruses, coxsackie, enteroviruses, and others, with mainly neurological complications. It could also be a new neuropathic virus, not recognized yet. We analyze the relationship between infections and high temperature. We point out the importance of the clinical history and knowledge of the pathophysiology of viral infections to diagnose these infections and the need to be prepared for a new epidemic with adequate infrastructure, equipments, medicines, and most important, training in early warning of the emergence of a new disease and rational therapeutics. The health programs had serious limitations to aid in this scenario. The best ways to prevent and control emerging infections is improving socioeconomic conditions of people, environmental sanitation and environmental condition. The cost of this epidemic was very high, with a high infantile mortality. We have to learn the lesson so it does not happen again.